THE INFLUENCE OF TECHNOLOGY USE ON THE EFFECTIVENESS OF ASSESSING SPEAKING SKILLS IN ENGLISH LANGUAGE LEARNING - Aisyah Rahmawati; Zuhri Efendi (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to determine the effect of using technology, especially the Duolingo application and YouTube learning videos, on the effectiveness of speaking skills assessment in English learning for students of class VIII-A SMPN 2 Susoh. The research method used a one-group pre-test and post-test pre-experiment design with a sample of 30 students selected purposively. The research instrument is a speaking test that assesses aspects of pronunciation, fluency, vocabulary, and grammar with a 1-5 scale rubric. The treatment was conducted through six sessions of technology-based learning, followed by a comparison of pre-test and post-test results. Data analysis using SPSS showed an increase in the average score from 61.87 in the pre-test to 78.23 in the post-test, or an increase of 26.45%. These results indicate that the use of technology can significantly improve the quality of assessment and students' speaking skills. The findings of this study recommend the utilisation of digital learning media as an alternative to more effective assessment methods, especially in junior high schools in non-metropolitan areas.